Carbon Nanotubes as Support in the Platinum‐Catalyzed Hydrolytic Dehydrogenation of Ammonia Borane. Issue 17 (9th June 2015) - Chen, Wenyao; Duan, Xuezhi; Qian, Gang; Chen, De; Zhou, Xinggui
Abstract We report remarkable support effects for carbon nanotubes (CNTs) in the Pt/CNT‐catalyzed hydrolytic dehydrogenation of ammonia borane. The origin of the support‐dependent activity and durability is elucidated by combining the catalytic and durability testing with characterization by a range of spectroscopy and high‐angle annular dark‐field scanning transmission electron microscopy techniques and ICP analysis. The effects mainly arise from different electronic properties and different abilities for the adsorption of boron‐containing species on platinum surfaces and changes in size and shape of the platinum particles during the reaction. Defect‐rich CNTs in particular are a promising support material, as it not only enhances the platinum binding energy, leading to the highest hydrogen generation rate, but also inhibits the adsorption of boron‐containing species and stabilizes the platinum nanoparticles to resist the agglomeration during the reaction, leading to the highest durability. The insights revealed herein may pave the way for the rational design of highly active and durable metal/carbon catalysts for the hydrolytic dehydrogenation of ammonia borane.